Inclusive search for the charmless radiative decay of the b-quark (b → sy) - Dova, María Teresa (1993)
We report on the search for the electromagnetic penguin decay b → sγ at √s ≈ mZ. We find no evidence for a signal and place an upper limit on the decay rate Br(b → sγ) < 1.2 × 10−3 at 90% C.L.